Verification of model wave heights with long-term moored buoy data: Application to wave field over the Indian Ocean. (1st August 2015) - Samiksha, S.V.; Polnikov, V.G.; Vethamony, P.; Rashmi, R.; Pogarskii, F.; Sudheesh, K.
Abstract: This paper describes the results obtained using a modified version (ModWAM) of the global wave model WAM, in which new parameterizations have been applied based on the seasonal changes and extreme weather events that have occurred in the Indian Ocean. Model significant wave heights ( H s ) have been verified using H s data extracted for the period 2000–2006 from 10 moored data buoys, deployed in the north Indian Ocean. Satellite altimeter H s has also been used for the model comparison. Based on the error estimates of significant wave heights and spectral wave energy, improvement achieved in wave prediction using ModWAM is demonstrated. We find that the ModWAM improved the accuracy of significant wave height prediction in deep water considerably (rmse of ModWAM is less than that of rmse of WAM), and provided better presentation for high waves that prevailed during southwest monsoon (e.g. H s, of the order of. 6.0 m in June 2005) and extreme weather events (e.g. cyclone that occurred in May 2005), compared to WAM; but, it still underestimates H s for high waves. Comparison between modeled and measured spectra shows that ModWAM overpredicts spectral energy at low frequencies, and underpredicts at high frequencies. Highlights: ModWAM wave model results were verified with moored buoy data of the Indian Ocean. New source function coefficients were applied in ModWAM based on physical processes. ModWAM improved the accuracy of significant wave height prediction in deep water. ModWAM reproduced high waves prevailed during monsoon and extreme events accurately. ModWAM overpredicts (underpredicts) spectral energy at low (high) frequencies.